Determination of PV Power and Battery Capacity Size for a Leisure Solar Powered Boat at Kalimas River, Surabaya, Indonesia - Nasirudin, Ahmad; Hasanudin, Hasanudin; Utama, Danu; Tahwoto, Lia Pundhi (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
As a green city, Surabaya had been developing a program of an environmentally friendly concept in almost all sectors. One of the developed sectors with this concept is the tourism area around the Kalimas river. Tour by riding a small passenger leisure boat is the most favorite recreational option. The leisure boat designs with environmentally friendly solar-powered concepts were developed, but regarding PV power and battery capacity determination, almost all designs are not optimal. This research is aimed to obtain the optimal PV power and battery capacity by calculating the number of PV panels and batteries with minimum cost. A Linear programming approach by Simplex method is applied in the optimization calculation. The results show that the number of the battery of the previous design can be reduced from 4 (four) units (20 kWh) becomes 3 (three) units (15 kWh) and the number of PV panels are still the same number with the previous one, i.e., 7 (seven) units (2,24 kW). The optimum system cost is around 264 million rupiahs, which means that the cost is reducing around 81 million rupiahs or 24%.